2016
DOI: 10.1152/ajpcell.00062.2016
|View full text |Cite
|
Sign up to set email alerts
|

Ketoisocaproic acid, a metabolite of leucine, suppresses insulin-stimulated glucose transport in skeletal muscle cells in a BCAT2-dependent manner

Abstract: Although leucine has many positive effects on metabolism in multiple tissues, elevated levels of this amino acid and the other branched-chain amino acids (BCAAs) and their metabolites are implicated in obesity and insulin resistance. While some controversies exist about the direct effect of leucine on insulin action in skeletal muscle, little is known about the direct effect of BCAA metabolites. Here, we first showed that the inhibitory effect of leucine on insulin-stimulated glucose transport in L6 myotubes w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 54 publications
1
45
0
Order By: Relevance
“…Emerging studies have shown that BCKAs alter carbohydrate metabolism in multiple insulin-responsive tissues (77), (78). BCKAs inhibit glucose uptake in cardiomyocytes (27) and skeletal muscle (79) and reducing BCKAs levels by cardiac-specific BCATm deletion has been attributed to improvement in basal and insulin-induced glucose oxidation along with increased ATP production (78).…”
Section: Discussionmentioning
confidence: 99%
“…Emerging studies have shown that BCKAs alter carbohydrate metabolism in multiple insulin-responsive tissues (77), (78). BCKAs inhibit glucose uptake in cardiomyocytes (27) and skeletal muscle (79) and reducing BCKAs levels by cardiac-specific BCATm deletion has been attributed to improvement in basal and insulin-induced glucose oxidation along with increased ATP production (78).…”
Section: Discussionmentioning
confidence: 99%
“…We utilized RNAi to deplete myoblasts of BCAT2, using lipofectamine RNAiMAX (Life Technologies). Briefly, 2.5 × 10 5 cells were seeded in 6‐well plates along with either scramble (control, Sigma #SIC001) or BCAT2 siRNA oligonucleotides (sense 5′‐CUAUGUGCGGCCGGUGCUU, anti‐sense 5′‐AAGCACCGGCCGCACAUAG) as described previously (Maeda, Abdullahi, Beatty, Dhanani, & Adegoke, ; Moghei et al, ). After 48 hr, cells were either harvested (D0 of differentiation) or washed twice with PBS and shifted into regular (complete) DM.…”
Section: Methodsmentioning
confidence: 99%
“…Branched‐chain amino acids (BCAA: leucine, isoleucine, and valine) alone or in combination with resistance exercise have anabolic effects on skeletal muscle. Consistent with this, BCAAs, and in particular leucine, can induce signaling that promotes muscle protein synthesis via the mammalian/mechanistic target of rapamycin complex 1 (mTORC1) (Anthony, Anthony, & Layman, ; Matsumoto et al, ), inhibit protein degradation via the ubiquitin‐proteasome system (Herningtyas et al, ), improve mitochondrial metabolism (D’Antona et al, ), and improve glucose transport and insulin signaling in some (Kleinert et al, ; Liu et al, ; Nishitani et al, ) though not all (Moghei, Tavajohi‐Fini, Beatty, & Adegoke, ) studies. Interestingly, many of the anabolic features of BCAA can be mimicked by metabolites of these amino acids.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…While a number of studies demonstrate that either amino acid mixture or BCAA supplementation have beneficial effects on protein turnover and muscle wasting in patients with cirrhosis, kidney failure, cancer, or sepsis, [14][15][16][17][18][19][20][21][22][23][24][25] mounting evidence suggests that amino acids/BCAAs or their metabolized keto acids lead to hyperactivation of mTOR signaling, 7,26-28 induction of oxidative stress, 29-32 mitochondrial dysfunction, 33,34 apoptosis, 35,36 and more importantly, insulin resistance and/or impaired glucose metabolism. 7,[26][27][28][37][38][39][40][41][42][43][44] Consistent with these findings, recent studies demonstrate that a BCAA metabolite elevated in diabetic individuals can drive vascular fatty acid transport in muscle and induce insulin resistance in mice 44 and a defective muscle BCAA metabolism induces impaired lipid metabolism and insulin resistance.45 On the other hand, deprivation of a single or all three BCAAs improves insulin sensitivity and glycemic control in either chow-or High-Fat Diet (HFD)-fed, or genetically diabetic rodents.46-48 These findings strongly indicate not only a correlative, but also a causative role of circulating BCAAs and their oxidized intermediates in the development of insulin resistance and diabetes. As such, it is important to advance our understanding of BCAA regulatory mechanisms that would allow us to explain the reasons for high circulating levels of BCAAs found in obese and diabetic individuals.…”
mentioning
confidence: 99%